Enhanced treatment of high-algae water and membrane fouling mitigation by SPDA@MIL-101-modified polyethersulfone ultrafiltration membranes with magnetic field regulation and magnetic flocculant assistance - Meng Yao; Ang Li; Zhilin Ran; Xiaoqing Dong; Ruiyan Xiang; Ting Chen; Gang Liu (Journal of Environmental Chemical Engineering, 2026)

Revealing thermoelectric property-performance correlations for the design of self-powered sensors - Zijian Lin; Bangzhou Tian; Xiaobo Tan; Chuke Zhao; Jiaxing Luo; Zhilong Zhao; Fan Feng; Qiang Sun; Ran Ang (Chemical Engineering Journal, 2026)

Interactive effects of noise and odor on construction workers' environmental perception and cognitive performance amid outdoor thermal stress - Zi Li; Xinyue Zhang; Zijing Peng; Ran Xing; Ang Li; Bo Hong (Building and Environment, 2026)

The DNA-binding protein PfAP2-V regulates erythrocyte invasion and pathogenesis of the human malaria parasite Plasmodium falciparum - Yanxin Zhang; Changhong Wang; Qilong Li; Ang Li; Yutao Zhang; Ziwei Su; Liying Yu; Kexin Zheng; Tong Liu; Ning Jiang; Yiwei Zhang; Xiaoyu Sang; et al. (Science China Life Sciences, 2026)

Isolation and identification of spoilage bacteria from kiwifruit and analysis of the antagonistic activity of three Bacillus strains against these bacteria - Ang Liu; Wen-xin Li; Yi Liu; Xing-lin Ran; Bo-yu Dong; Qiu-ping Yao; De-quan Zhu (Food Control, 2026)

A laser with instability reaching 4 × 10 - 17 based on a 10-cm-long silicon cavity at sub-5-K temperatures - Zhi-Ang Chen; Hao-Ran Zeng; Wen-Wei Wang; Han Zhang; Run-Qi Lei; Jian-Zhang Li; Cai-Yin Pang; She-Song Huang; Xibo Zhang (Science Bulletin, 2025)

Synergistic experimental-numerical investigation of performance optimization and dynamic behavior in perforated electrode electrocoagulation systems for emulsified oil wastewater remediation - Ang Li; Bing Wang; Meng Yao; Zhilin Ran; Zheng Ju; Ting Chen (Process Safety and Environmental Protection, 2025)

Mechanism of improved cellulase production by Trichoderma reesei in water-supply solid-state fermentation - Wenjing Xue; Yiru Sheng; Yukai Tai; Juan Ding; Ran He; Yale Jiang; Bangchao Zhong; Jian He; Ang Ren; Qin He (Bioresource Technology, 2025)

Thermoelectric cooling and low-temperature power generation in n-type PbTe enabled by band flattening and entropy engineering - Qian Deng; Jiansen Wen; Xiang An; Yin Xie; Jiaxing Luo; Zhilong Zhao; Baisheng Sa; Hongliang Dong; Ran Ang (Chemical Engineering Journal, 2025)

The zinc-finger transcription factor ZFP8 negatively regulates the drought stress response in Arabidopsis thaliana by inhibiting the transcriptional activity of ABF2 - Yu'ang Tian; Yanling Li; Kelan Wang; Ran Xia; Yingru Lin; Guohui Pan; Haoyu Shi; Dawei Zhang; Honghui Lin (Journal of Plant Physiology, 2024)

Exceptional thermoelectric and mechanical performance in (Bi, Sb)2Te3 matrix facilitated by AgInSe2 alloying - Ruiheng Li; Wenxin Ou; Jianglong Zhu; Qian Deng; Xiaobo Tan; Qi Zhao; Tianbo Lu; Shaojingya Gao; Huangshui Ma; Hao Wu; Qiang Sun; Ran Ang (Chemical Engineering Journal, 2024)

Functionally separated electronic band engineering via multi-element doping plus high-density defects advances board-temperature-range thermoelectric performance in GeTe - Jianglong Zhu; Xiaobo Tan; Dong Pan; Yanni Luo; Ruiheng Li; Xuri Rao; Ruihuan Cheng; Chengliang Xia; Yue Chen; Qiang Sun; Ran Ang (Chemical Engineering Journal, 2024)

Combined toxic effects of nanoplastics and norfloxacin on mussel: Leveraging biochemical parameters and gut microbiota - Ran Xu; Li'ang Li; Jiahui Zheng; Chenglong Ji; Huifeng Wu; Xiang Chen; Yuchuan Chen; Menghong Hu; Elvis Genbo Xu; Youji Wang (Science of The Total Environment, 2023)

Experimental and Numerical Studies on Bending and Failure Behaviour of Inflated Composite Fabric Membranes for Marine Applications - Yunling Ye; Jin Gan; Huabing Liu; Qingfei Guan; Zhongyi Zheng; Xiaolin Ran; Zi’ang Gao (Journal of Marine Science and Engineering, 2023)
Owing to their excellent physical characteristics of lightweightiness, compactness and rapid deployment, the inflated membrane structures satisfy the demands of maritime salvage and military transportation for long-distance delivery and rapid response. Exploring the failure behaviour of inflated membrane structures can greatly contribute to their widespread applications in ocean engineering. In this research, the main objective is to comprehensively investigate the bending and failure behaviour of inflated membrane structures. Thus, the Surface-Based Fluid Cavity method is employed to set up the finite element model (FEM) which is compared to the experimental results to verify its reliability. In parallel, the effects of internal pressure and wrinkles are discussed. An empirical expression of the ultimate bending loading was fitted by face-centred composite designs of the Response Surface Methodology. The results of experiments and FEM show that the bearing capacity of the inflated membrane structure is positively correlated with the internal pressure but decreased obviously with the occurrence and propagation of wrinkles. The deformation behaviour and the stress distribution are similar to those of the traditional four-point bending beam, and the local instability induced by wrinkles will cause structural failure. In addition, the numerical model and the proposed expression showed deviations below 5% in relation to the experimental measures. Therefore, the FEM and proposed expression are high of reliability and have important engineering guiding significance for the application of inflated membrane structures in ocean engineering.

Deduction and exploration of the evolution and function of vertebrate GFPT family - Si-ang Wei; Ran Xu; Yu-yao Ji; Zhi-wen Ding; Yun-zeng Zou (Genes & Genomics, 2022)

Al(III)-binding properties at the molecular level of soil DOM subjected to long-term manuring - Jianchao Zhang; Ang Hu; Boren Wang; Wei Ran (Journal of Soils and Sediments, 2019)